THE SELECTION OF INVESTMENT PROPOSALS AT PRE-INVESTMENT STAGE IN THE FORMATION OF INVESTMENT PROGRAMS OF ROAD CONSTRUCTION - O. Gorelova (Вестник университета)
The classification features of investment proposals are determined. Tasks and procedure of the examination of investment projects are shown. The algorithm of examination of received investment proposals is considered.